Why is the timing of school tracking so heterogeneous? - Kenn Ariga; Giorgio Brunello; Roki Iwahashi; Lorenzo Rocco (Institute for the Study of Labor (IZA), 2005)
Secondary schools in the developed world differ in the degree of differentiation and in the first age of selection of pupils into different tracks. In this paper, we account for the heterogeneity of tracking time with a simple stochastic model which conjugates the returns from specialization with the costs of early selection. We calibrate the model for 20 countries including most of Europe, the US and Japan and show that the model performs rather well in replicating the observed heterogeneity, with the remarkable exception of Germany.
Keywords: H52; H73; 330; tracking; secondary schools